Optimal DL-Methionyl-DL-Methionine Supplementation Improved Intestinal Physical Barrier Function by Changing Antioxidant Capacity, Apoptosis and Tight Junction Proteins in the Intestine of Juvenile Grass Carp (Ctenopharyngodon idella) - Pei Wu; Yuening Su; Lin Feng; Weidan Jiang; Shengyao Kuang; Ling Tang; Jun Jiang; Yang Liu; Xiaoqiu Zhou (MDPI AG, 2022)
The present study was a part of a larger research project that aimed to investigate the effects of Met-Met supplementation on fish growth and intestinal health. This study mainly focused on the relationship between dietary Met-Met and intestinal physical barrier function in fish. Seven iso-nitrogenous diets supplemented with 2.50 g/kg DL-methionine (DL-Met) and six graded levels of Met-Met (0.00, 0.79, 1.44, 1.84, 2.22, and 2.85 g/kg) were used to feed juvenile grass carp for 10 weeks, after which a 14-day Aeromonas hydrophila challenge test was performed. The results indicated that optimum levels of Met-Met decreased intestinal oxidative damage, probably by increasing total antioxidant capacity, and the activity and gene expression levels of several antioxidant enzymes, which were closely related to the changed Nrf2/Keap1 signaling. Meanwhile, optimum levels of Met-Met decreased intestinal apoptosis and improved the intestinal tight junction, as evident by the downregulated mRNA levels of initiator and executioner caspases; the pro-apoptotic-related proteins FasL, Apaf-1, and Bax; and upregulated mRNA levels of the anti-apoptotic proteins Bcl-2, Mcl-1b, and IAP and the TJ proteins claudins, occludin, and ZOs. Furthermore, the positive effects of Met-Met on improving intestinal physical barrier function were superior to those of DL-Met in fish. These findings showed that optimal Met-Met supplementation improved intestinal physical barrier function, probably by changing antioxidant capacity, apoptosis, and tight junction proteins in fish.